2005
DOI: 10.1016/j.jbi.2004.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for rapid outbreak detection: a research synthesis

Abstract: The threat of bioterrorism has stimulated interest in enhancing public health surveillance to detect disease outbreaks more rapidly than is currently possible. To advance research on improving the timeliness of outbreak detection, the Defense Advanced Research Project Agency sponsored the Bio-event Advanced Leading Indicator Recognition Technology (BioALIRT) project beginning in 2001. The purpose of this paper is to provide a synthesis of research on outbreak detection algorithms conducted by academic and indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 31 publications
2
138
0
1
Order By: Relevance
“…Jenkins (2000) used integer programming to identify a small subset of oil spills that are similar to all potential categories of spills to predict the type of pollutant a terrorist group might use. Buckeridge et al (2005) classified bioterrorism outbreak algorithms and found that spatial and other covariate information can improve measures for detecting and evaluating outbreaks. Stuart and Wilkening (2005) used first-and second-order catastrophic decay models to study the impact of degradation of biological-weapons agents leaked into the environment.…”
Section: Countermeasures Portfoliosmentioning
confidence: 99%
“…Jenkins (2000) used integer programming to identify a small subset of oil spills that are similar to all potential categories of spills to predict the type of pollutant a terrorist group might use. Buckeridge et al (2005) classified bioterrorism outbreak algorithms and found that spatial and other covariate information can improve measures for detecting and evaluating outbreaks. Stuart and Wilkening (2005) used first-and second-order catastrophic decay models to study the impact of degradation of biological-weapons agents leaked into the environment.…”
Section: Countermeasures Portfoliosmentioning
confidence: 99%
“…We adopted the approach of evaluating sensitivity at a fi xed 1% alert rate defi ned empirically for each algorithm and dataset, as used by Jackson et al (12). Our approach is in accord with a recent review that recommended basing alert thresholds on empirical data rather than on classical statistical theory (17). A major strength of the study is that BioSense is a national system that provided access to 2 major datasets with differing characteristics and to data from hundreds of facilities in many states.…”
Section: Discussionmentioning
confidence: 99%
“…The Praedico™ ML layer was trained by utilizing hundreds of false positive and true positive syndromic alerts. To guarantee high detection recall, the Praedico™ algorithm leverages many known detection algorithms, including versions of CDC, CUSUM, EWMA, and regression models [2]. The ML model combines these models and uses additional time series features to detect anomalies and user feedback received on previous alerts (high confidence alerts).…”
Section: Methodsmentioning
confidence: 99%